Statins- the future of Alzheimer’s disease treatment? - O’Connell, Florence (Trinity Student Medical Journal, 2006)
Emerging research indicates that the pathological basis of Alzheimer’s disease maybe inflammatory in origin, possibly mediated through the pro-inflammatory cytokine, interleukin-1beta. Statins are a class of drugs which reduce circulating lipid levels. There is also evidence that they may have anti-inflammatory properties. This review assesses new evidence that statin therapy may have a role in the treatment of Alzheimer’s disease.